Cashew nut "bits and pieces" for cashew nut butter spread processing - Tansiongco, Johnny Perez (2001.)
Three formulations of cashew nut butter spread varying in their salt content were prepared.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Cashew nut